Features of forecasting modern stock market crises - Korneliuk, Olga; Khirova, Viktoria (Херсонський державний університет, 2020)
In the scientific work, the essence of the concept of the stock market crisis is investigated and the premises and causes of the modern stock market crash of 2020 are analyzed. In particular, the theoretical foundations and practical aspects of the emergence and develop-ment of exchange crises are described in terms of their key characteristics. Also, stock indices, that form the market prices of securities and on the basis of which it is possible to monitor the volatility of the stock market, are analyzed. The dynamics of the largest falls of the Dow Jones stock exchange index is studied and a detailed description of the causes and consequences of each fall is presented. Based on the results of the analysis, the main prerequisites for the modern stock market crisis of 2020 are determined.
Keywords: stock market crisis; stock market crash; Dow Jones index; coronavirus; negative stock market dynamics; 336.7:33.05-044.372